Generalized Design of Shunt Active Power Filter with Output LCL Filter - Hou, Rui; Wu, Jian; Liu, Yuchao; Xu, Dianguo (Elektronika ir Elektrotechnika, 2014)
This paper analyses the characteristics of LCL filter in active power filter (APF) and provides an accurate formula to determine the resonant frequency of system. Based on a single-phase equivalent circuit model, a systematic approach to design APF with LCL filter is proposed. Total inductance is determined by the capability of APF. Moreover, damping ratio, resonant frequency and attenuation degree of switching ripples are the most crucial factors to design parameters of LCL filters. A method to consider them comprehensively is provided. Meanwhile, LCL filter deteriorates the compensation effect of APF. To address this problem, a novel control strategy is presented to correct the magnitude and phase of output current. Simulation and experimental results demonstrate the validity of proposed methods. DOI: http://dx.doi.org/10.5755/j01.eee.20.5.3910